Dinamika Perkembangan Fakultas Menuju Pusat Studi Islam yang Unggul dan Modern - Bariyah, Oneng Nurul; ., Romlah; ., nurhadi (Asosiasi Dosen Peneliti Ilmu Keislaman dan Sosial, 2024)
This research aims to describe the history of the establishment of the Faculty of Islamic Studies at Muhammadiyah University Jakarta and the dynamics that occur towards a Centre for Excellent and Modern Islamic Studies. The research was conducted at the Faculty of Islamic Studies, Muhammadiyah University Jakarta. The study uses a historical approach so that the main sources are documents in the form of official letters, memories, diaries, meeting minutes, decision letters, dispositions, and so on. Other data were obtained from interviews. The research findings show that the forerunner of the Faculty of Islamic Religion UMJ began in 1962 and officially became the Faculty of Islamic Religion on 20 November 1996 and became one of the icons of the Muhammadiyah Higher Education Institution as a metamorphosis of the Faculty of Tarbiyah, Sharia and Da'wah. The efforts of the leadership of the Faculty of Islamic Religion gave birth to new study programmes so that FAI has 6 undergraduate study programmes and one master programme. The seriousness of the academic community of the Faculty of Islamic Religion resulted in accreditation ratings for all study programmes and Superior predicates for the Sharia Banking Study Programme and Master of Islamic Studies.